Does economic uncertainty affect the decision to bear children? Evidence from East and West Germany - Sumon Kumar Bhaumik; Jeffrey B. Nugent (Institute for the Study of Labor (IZA), 2005)
Although economic agents routinely face various types of economic uncertainty, their effects are often unclear and hard to assess, in part due to the absence of suitable measures of uncertainty. Because of the numerous and very substantial institutional changes that people in the transition economies of Central and Eastern Europe experienced during the last two decades, these countries are excellent candidates for examining the effects of uncertainties on various kinds of behavior. During their periods of uncertainty, moreover, these countries have experienced sharply falling fertility rates. Some have argued that these two phenomena are linked but others have remained skeptical in view of the fact that the evidence is largely confined to the macro level. This paper demonstrates the existence of such a link at the micro level using two different types of uncertainty measures based on GSOEP data from Eastern (and for comparison purposes also Western) Germany for the years 1992-2002. The results suggest that employment uncertainty (but not financial uncertainty) was considerably greater in Eastern Germany during its transition than in Western Germany and had a highly nonlinear effect on the probability of a birth in any period. The result is rather robust to differences in specification and suggests that the higher employment uncertainty in East Germany in the transition could have contributed significantly to the sharp fall and unusually low level of its fertility. In view of the results, we argue that an options based theory is perhaps a richer analytical paradigm for a discussion of fertility decisions in a rapidly changing environment than the traditional Beckerian theory.
Keywords: J13; J22; D81; 330; falling fertility; uncertainty; Germany; Wirtschaftliche Instabilität; Fruchtbarkeit; Familienökonomik; Schätzung; Neue Bundesländer; Alte Bundesländer